IL-6/STAT3 Is a Promising Therapeutic Target for Hepatocellular Carcinoma - Xu, Junnv; Lin, Haifeng; Wu, Gang; Zhu, Mingyue; Li, Mengsen (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is a common malignant tumor of which the occurrence and development are complex processes involving multistep and multifactor interactions. Interleukin-6 (IL-6), a multifunctional inflammatory cytokine, has increased expression in hepatocellular carcinoma and is closely related to the occurrence of HCC and patient prognosis. IL-6 plays a role by binding to the IL-6 receptor (IL-6R) and then triggering the JAK kinase associated with the receptor, stimulating phosphorylation and activating signal transducer and activator of transcription 3(STAT3) initiation downstream signals, participating in the processes of antiapoptosis, angiogenesis, proliferation, invasion, metastasis, and drug resistance of tumor cells. It is important to treat HCC by blocking the IL-6/STAT3 signaling pathway. Overall, consideration of the IL-6/STAT3 signaling pathway and its role in the genesis and progression of HCC will contribute to the development of potential drugs for targeting treatment of liver cancer.